Prediction model construction for the occurrence of LARS after neoadjuvant therapy combined with laparoscopic total mesorectal excision in male patients with mid-low rectal cancer - Wang, Deng-Chao; Peng, Xue-Feng; Yu, Miao (Frontiers in Oncology, 2024)
BackgroundNeoadjuvant chemoradiotherapy for rectal cancer improves surgical outcomes and reduces recurrence but can cause low anterior resection syndrome (LARS), affecting quality of life. This study aims to predict the risk of LARS in male patients with mid-low rectal cancer after laparoscopic total mesorectal excision (TME).MethodsClinical data from 203 male patients with mid-low rectal cancer who underwent neoadjuvant therapy and laparoscopic resection were collected. Patients were divided into training (n=143) and validation (n=60) cohorts. LARS risk factors were identified using logistic regression, and a predictive model was constructed and validated using ROC curve, Hosmer-Lemeshow test, calibration curve, and decision curve analysis (DCA).ResultsLARS occurred in 53.6% of the patients in this study. Multivariate logistic regression analysis revealed that BMI ≥ 25 kg/m², tumor distance from the anal margin < 5 cm, radiotherapy, and anastomotic leakage were independent risk factors for postoperative LARS in patients (P < 0.05). The areas under the ROC curves for the training cohort and validation cohort were 0.866 (95% CI: 0.807-0.925) and 0.724 (95% CI: 0.595-0.853), respectively, with both groups showing good goodness-of-fit test results (P > 0.05). The DCA curve indicated that the model had a high clinical utility.ConclusionsBMI ≥ 25 kg/m², tumor distance from the anal margin < 5 cm, radiotherapy, and anastomotic leakage are independent risk factors for the occurrence of LARS after neoadjuvant therapy combined with laparoscopic TME in male patients with mid-low rectal cancer. These factors should be emphasized in clinical practice, and corresponding preventive measures should be promptly implemented.